THE FOURTH INDUSTRIAL REVOLUTION „INDUSTRY 4.0” - Alin STĂNCIOIU (Fiabilitate şi Durabilitate)
The many observers estimate that in the world is at the beginning of a new industrial revolution, which it is considered the fourth revolution and it is called "Industry 4.0". The connecting many products to the internet, presence of sensors, wireless communications expansion, robot and intelligent machine development, real-time data analysis have the potential to turn the way the production is done. Connecting the physical world to the virtual world in cyber-physical systems it will have a disruptive impact on technologies, manufacturing processes and people.